Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.12811/kshsm.2014.8.1.075
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Its Correlated Factors among Elderly People with Diabetes in a Community

Abstract: The purpose of this study was to examine the factors affecting quality of life among elderly people with type 2 diabetes mellitus (DM) in a community. The design of this study was an exploratory survey. The subjects were 268 adults aged over 65 years with DM in a community. The data were collected from July to October, 2011 and analyzed by descriptive statistics, Pearson's correlation coefficient, and stepwise multiple regression by using SPSS/WIN 20.0 program. The quality of life was positively associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This study identified significant differences in health information literacy based on the participants' level of education, corroborating the findings of previous studies [27,31] that higher education levels correspond to increased health information literacy. Furthermore, while no difference was observed in the participants' occupation in the post-test, a significant difference was noted in relation to occupation.…”
Section: Chnrsupporting
confidence: 90%
See 2 more Smart Citations
“…This study identified significant differences in health information literacy based on the participants' level of education, corroborating the findings of previous studies [27,31] that higher education levels correspond to increased health information literacy. Furthermore, while no difference was observed in the participants' occupation in the post-test, a significant difference was noted in relation to occupation.…”
Section: Chnrsupporting
confidence: 90%
“…Furthermore, while no difference was observed in the participants' occupation in the post-test, a significant difference was noted in relation to occupation. Kim et al's study [31] reported variations in health information literacy due to job characteristics in South Korea. Specifically, technical workers, agricultural workers, fishery workers, and self-employed individuals scored less than 30 out of 50, indicating lower health information literacy compared to office workers.…”
Section: Chnrmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher score reflects better diabetes self-management. A previous K-SDSCA validation study reported acceptable reliability for this scale, obtaining a Cronbach's alpha coefficient of >0.76 (Chang & Song 2009;Kim, Seo, Kim, Park, & Kang, 2014). In this study, the Cronbach's alpha coefficient was 0.77.…”
Section: Diabetes Self-management Behaviorssupporting
confidence: 50%
“…Older adults with DM have a poorer overall QoL compared with those without DM (Kim et al, 2014 ; Lee & Kim, 2017 ). Previous studies have suggested that HR–QoL in older adults with DM is associated with various factors: health behaviours such as nutrition, physical activity, smoking, stress and nutrition; socio‐psychological factors such as depression, anxiety, fatigue, social support, self‐esteem; demographics and economic status; and glycemic control and DM‐related complications (Kim et al, 2014 ; Lee, 2013 ; Lim & Oh, 2013 ; Scollan‐Koliopoulos et al, 2013 ; Shin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%